Rapid purification of protein complexes from mammalian cells - Medina, Dan (Oxford University Press, 2000)
The evaluation of the protein binding partner(s) of biologically important proteins is currently an area of intense research, especially since the development of the yeast two-hybrid assay. However, not all protein–protein interactions uncovered by this assay are biologically relevant and another confirmatory assay must be performed. Ideally, this assay should be rapid, versatile and performed under conditions which mimic the ‘normal’ physiological state as closely as possible. Towards this goal, we have constructed two eukaryotic expression vectors that facilitate the purification of a protein of interest, along with any associated proteins, from mammalian cells. These vectors incorporate the following features: (i) a tetracycline-responsive promoter so that the level of protein production can be regulated; (ii) an N-terminal glutathione S-transferase tag or a triple repeat of the HA1 epitope, to facilitate purification of the protein either by glutathione affinity chromatography or immunoprecipitation, respectively, followed by a multiple cloning site; (iii) the gene for the enhanced green fluorescent protein (for detection of the presence of the fusion protein and subcellular localization); (iv) a puromycin marker for the selection of stable transformants; (v) a truncated EBNA protein and oriP sequence for episomal replication of the vector. These latter two features permit expansion of small cultures of transfected cells under puromycin selection, thereby increasing the amount of tagged protein that can be purified. We show that these vectors can be used to direct the doxycycline-inducible expresssion of tagged proteins and to recover tagged CIP1–p21 protein complexes from HeLa cells. Furthermore, we show that these tagged p21-purified complexes contain both cyclin A and Cdk2, which are known to interact with p21, but not β-actin.